Mobile stroke units for prehospital thrombolysis, triage, and beyond: benefits and challenges. Issue 3 (March 2017) - Fassbender, Klaus; Grotta, James C; Walter, Silke; Grunwald, Iris Q; Ragoschke-Schumm, Andreas; Saver, Jeffrey L
Summary: In acute stroke management, time is brain. Bringing swift treatment to the patient, instead of the conventional approach of awaiting the patient's arrival at the hospital for treatment, is a potential strategy to improve clinical outcomes after stroke. This strategy is based on the use of an ambulance (mobile stroke unit) equipped with an imaging system, a point-of-care laboratory, a telemedicine connection to the hospital, and appropriate medication. Studies of prehospital stroke treatment consistently report a reduction in delays before thrombolysis and cause-based triage in regard to the appropriate target hospital (eg, primary vs comprehensive stroke centre). Moreover, novel medical options for the treatment of stroke patients are also under investigation, such as prehospital differential blood pressure management, reversal of warfarin effects in haemorrhagic stroke, and management of cerebral emergencies other than stroke. However, crucial concerns regarding safety, clinical efficacy, best setting, and cost-effectiveness remain to be addressed in further studies. In the future, mobile stroke units might allow the investigation of novel diagnostic (eg, biomarkers and automated imaging evaluation) and therapeutic (eg, neuroprotective drugs and treatments for haemorrhagic stroke) options in the prehospital setting, thus functioning as a tool for research on prehospital stroke management.